The mediating role of self-control between physical activity and mobile phone addiction in adolescents: a meta-analytic structural equation modeling approach - Lin, Hao; Fan, Huailong; Fu, Qi; Li, Shan; Liu, Qingzao (Frontiers in Psychiatry, 2025)
Background and objectivesWith the rapid advancement of information technology, adolescent cell phone addiction has emerged as a pressing and urgent issue. The combined influence of physical activity (PA) and self-control (SC) on mobile phone addiction (MPA) in adolescents has been investigated in previous studies. However, the strength of the relationship between physical activity and cell phone addiction is not clearly understood. The mediating effect of self-control on this relationship also lacks clarity. Thus, in this study, meta-analytic structural equation modeling methods were employed to evaluate the reliability of effect sizes and the mediating effect of SC.MethodsRelevant manuscripts from the establishment of databases up to May 2024 were retrieved from five Chinese and English databases: Web of Science, PsycINFO, Pubmed, CNKI (core), and CBM. Meta-analysis was performed using CMA (V3) software, while the Web MASEM application was used to perform path analysis and mediated effects analysis.ResultsThis meta-analysis included a total of 48 studies containing 75,541 subjects. The findings of this study revealed that the mean weighted effect size of PA and MPA was -0.204, thereby indicating a low to moderate negative correlation between the two parameters. Meanwhile, the mean weighted effect size of PA and SC was 0.213, which was indicative of a small to medium strength positive correlation between the two. However, SC and MPA were found to share a medium to large strength negative correlation, as revealed by the mean weighted effect size of -0.449. Structural equation model (SEM) results demonstrated that the mediating effect of SC between PA and MPA was -0.091, with the mediating effect having a share of 49.7%.ConclusionAdolescent PA and MPA exhibited a low to moderate negative correlation, with SC acting as a partial mediator between the two.